The Secret Garden (for grade 7) - Burnett Hodgson Frances (Pakistan Oxford University Press, 2025)
The Secret Garden by Frances Hodgson Burnett is a classic children$1 (Bs novel about friendship, healing, and the power of nature. The story follows Mary Lennox, a spoiled and lonely girl sent to live with her uncle in a gloomy English mansion after her parents die. There, she discovers a hidden, locked garden that has been neglected for years. With the help of her cousin Colin, who is sickly and bedridden, and a kind local boy named Dickon, Mary brings the garden back to life. As the garden blooms, the children also grow healthier, happier, and stronger, showing how love, care, and the beauty of nature can heal both the body and the heart.s
oung Jim Hawkins discovers a treasure map in the chest of a deceased pirate. He joins a voyage on the ship Hispaniola to find the treasure, led by Captain Smollett. Among the crew is the cunning Long John Silver, who secretly leads a group of mutineers. On the island, battles break out between the honest crew and the pirates. After many adventures, Jim helps secure the treasure, and they return to England, leaving some mutineers behind.